Dynamics of Capability Upgrading in Indonesian Herbal Medicine Firms - Erman Aminullah (STI Policy and Management Journal, 2022)
This article examined the dnamics of capability upgrading in Indonesian herbal medicine firms for empirical and future trends analysis. The dynamics of capability upgrading was analysed by using system dynamics modelling.  New knowledge was revealed from system  dynamics analysis of capability upgrading in Indonesian herbal medicine firms, the core ideas are: capability upgrading in Indonesian herbal medicine firms   can be realized by two routes: i. the linier moving up of  technological capability ladders from traditional herbal  to standardized herbal and phytopharmaceutical medicine, and, ii.  the non-linier dynamic of technological capability upgrading by directly producing standardized herbal by using R&D and then move-up to create phytopharmaceutical medicine.  The enabler factors of company’s success in capability upgrading were innovation collaboration and management coordination led by top management. The process of  capability upgrading can be accelareted by  incporporating: advanced knowledge base (such as biotechnology), the entrepreneurial activities of leading firms, and institutional/regulatory support from the government.. Keywords: capability upgrading, herbal medicine, system dynamics, future trends, enabler factors.